Testicular Ischemia Caused by Incarcerated Inguinal Hernia in Infants: Incidence, Conservative treatment procedure, and Follow-up - Ozdamar, Mustafa Yasar; Karakus, Osman Zeki (Urology Journal, 2017)
Purpose: Testicular ischemia and necrosis, especially in the infant age, may result from incarcerated inguinal hernia. Duration of ischemia is a significant factor for the affected testicle. We aimed to present a case series on the conservative management in the testicular ischemia caused by incarcerated inguinal hernia. Materials and Methods: Inguinal hernia repairs performed in between March 2009 and December 2014 were investigated retrospectively. Patients’ characteristics, hernia side, incarceration, testicular ischemia and complications were recorded. Color Doppler ultrasonography was performed in the incarcerated inguinal hernia patients preoperatively and was repeated on 3 and 7 days and then at 1, 3 and 6 months postoperatively. The testicle sizes, volumes, and arterial flow patterns of them were recorded at the same time. Results: Total 785 inguinal hernias were treated in 738 male patients, ranging from 18 days to 16 years. From all male patients, 44 (5.9%) had the IIH. There were 16 (36.3%) irreducible hernias in 44 incarcerated hernia patients. Of these 16, testicular ischemia was determined in 9 (56.2%) infants with the irreducible incarcerated hernia. Orchidopexy procedure was performed in these patients. Testicular atrophy was occurred in two patients (22.2%). In the others, testicular volumes and perfusions were normal during follow-up (mean 8.3 ± 2.2 months). Conclusion: Testicular ischemia resulting from incarcerated inguinal hernia may be treated conservatively without orchiectomy for the ischemic testicle and testicular ischemia may be followed with color Doppler ultrasound for at least 6 months. The inguinal hernia repair in infants should be subject to urgent surgery rather than elective surgery. So, the testicular ischemia in infants with the inguinal hernia will be an avoidable complication.